2022
DOI: 10.1128/spectrum.02264-21
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA Load and Infectivity of SARS-CoV-2 in Paired Respiratory and Oral Specimens from Symptomatic, Asymptomatic, or Postsymptomatic Individuals

Abstract: The dynamics of infection with SARS-CoV-2 have a significant impact on virus infectivity and in the diagnostic sensitivity of molecular and classic virus detection tests. In the present study we determined the diagnostic sensitivity of paired respiratory (nasopharyngeal and anterior nares swabs) and oral secretions (saliva and sublingual swab) and assessed infectious virus shedding patterns by symptomatic, asymptomatic, or postsymptomatic individuals.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Viral propagation in culture was also achieved more frequently in samples from the immunosuppressed group. All these findings were consistent with earlier reports [1,[27][28][29]. In immunocompetent patients, considering only samples collected ten or more days after onset of disease, 3.6%, 1.9% and 0.25% of blood, anal and urine samples were positive for SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 92%
“…Viral propagation in culture was also achieved more frequently in samples from the immunosuppressed group. All these findings were consistent with earlier reports [1,[27][28][29]. In immunocompetent patients, considering only samples collected ten or more days after onset of disease, 3.6%, 1.9% and 0.25% of blood, anal and urine samples were positive for SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 92%
“…The anatomical site chosen to collect the swab specimen for detection of SARS-CoV-2 might influence viral load detection. Higher RNA viral load was reported from nasopharyngeal than oropharyngeal swabs 28,124,181 . As a result, nasopharyngeal samples show the highest diagnostic accuracy compared with other upper respiratory tract samples 182 .…”
Section: Specimen Selection Sitementioning
confidence: 95%
“…As a result, nasopharyngeal samples show the highest diagnostic accuracy compared with other upper respiratory tract samples 182 . Similarly, higher virus isolation success was reported from nasopharyngeal swabs than from saliva, nasal or sublingual swabs 124 . However, another study found higher RNA viral loads in the throat and sputum than from nasal swabs 30 .…”
Section: Specimen Selection Sitementioning
confidence: 97%
See 1 more Smart Citation
“…Finally, we mainly collected saliva samples rather than NP swabs because the latter are logistically challenging in longitudinal sampling. As there is a lower chance of successful virus isolation from saliva sample, 28 our study may have underestimated the probability of viable virus shedding.…”
Section: Discussionmentioning
confidence: 84%